Cerebrospinal Fluid Leak after Transsphenoidal Surgery: A Systematic Review and Meta-analysis - Slot, Emma M.H.; Sabaoglu, Rengin; Voormolen, Eduard H.J.; Hoving, Eelco W.; van Doormaal, Tristan P.C. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background Cerebrospinal fluid (CSF) leak is widely recognized as a challenging and commonly occurring postoperative complication of transsphenoidal surgery (TSS).The primary objective of this study is to benchmark the current prevalence of CSF leak after TSS in the adult population.Methods The authors followed the PRISMA guidelines. The PubMed, Embase, and Cochrane Library databases were searched for articles reporting CSF leak after TSS in the adult population. Meta-analysis was performed using the Untransformed Proportion metric in OpenMetaAnalyst. For two between-group comparisons a generalized linear mixed model was applied.Results We identified 2,408 articles through the database search, of which 70, published since 2015, were included in this systematic review. These studies yielded 24,979 patients who underwent a total of 25,034 transsphenoidal surgeries. The overall prevalence of postoperative CSF leak was 3.4% (95% confidence interval or CI 2.8–4.0%). The prevalence of CSF leak found in patients undergoing pituitary adenoma resection was 3.2% (95% CI 2.5–4.2%), whereas patients who underwent TSS for another indication had a CSF leak prevalence rate of 7.1% (95% CI 3.0–15.7%) (odds ratio [OR] 2.3, 95% CI 0.9–5.7). Patients with cavernous sinus invasion (OR 3.0, 95% CI 1.1–8.7) and intraoperative CSF leak (OR 5.9, 95% CI 3.8–9.0) have increased risk of postoperative CSF leak. Previous TSS and microscopic surgery are not significantly associated with postoperative CSF leak.Conclusion The overall recent prevalence of CSF leak after TSS in adults is 3.4%. Intraoperative CSF leak and cavernous sinus invasion appear to be significant risk factors for postoperative CSF leak.
Keywords: complications; CSF leak; endonasal; liquorrhea; pituitary adenoma surgery; skull base